The Relationship between Students' 21st Century Skills and Learning Outcomes on Virus Material for Grade X of Senior High School Stage E - Rina Widiana; Diana Susanti; Yola Asri (Jurnal Penelitian Pendidikan IPA, 2025)
This study investigates the relationship between 21st-century skills and students’ learning outcomes on the topic of viruses in Grade X at SMA Negeri 1 Rao, Pasaman Barat, Indonesia. Employing a quantitative approach with a correlational research design, data were obtained from two instruments: a 21st-century skills questionnaire and a summative test on the virus topic. The questionnaire measured four core dimensions: critical thinking, creativity, collaboration, and communication. Data analysis was conducted using Pearson’s product–moment correlation to assess the strength and significance of the relationship between the variables. The results indicated a very weak and statistically non-significant correlation between 21st-century skills and summative learning outcomes. These findings suggest that while 21st-century skills are vital for fostering deep conceptual understanding and the practical application of scientific knowledge, they are not adequately captured by assessments focused primarily on rote memorization and factual recall. The study highlights the need for integrating learning approaches that embed competency-based evaluation, such as project-based learning, case studies, and collaborative problem-solving tasks. Such approaches would enable a more comprehensive measurement of students’ abilities and better align assessment practices with the demands of contemporary education